Development of motor skills applied to basketball in the developmental age - Montella, M.; Ceciliani, A.; Morsanuto, S.; Federici, A.; Altavilla, G. (Journal of Human Sport & Exercise, 2019)
Usually, the training planning large amounts of technical skills and tactical work are planned, neglecting the part of athletic physical training, while it is necessary to combine the athletic phase with the technical one according to principle of the complexity of the sports performance that integrates the quantitative part with to the qualitative one. The study aims to show whether specific workouts aimed at developing and consolidating the basic motor patterns then lead to an improvement in performance in basketball, which is not only athletic but also technical and tactical components. Surveys were carried out every two months taking into account the evolutionary phase of the athletes, monitored on height and weight, in some there was an improvement and then a deterioration, while for others there was a constant improvement. This study helps to use the test administration method to monitor the correlation between training and performance activities.